2017
DOI: 10.15226/2378-1726/4/5/00171
|View full text |Cite
|
Sign up to set email alerts
|

The Treatment of Hori's Nevus by New Combination Treatment without Side Effects: Dr. Hoon Hur's Golden Parameter Therapy and Dr. Hoon Hur's Optimal Melanocytic Suicide-2 Parameter Therapy

Abstract: Hori's nevus is an acquired benign dermal melanocytosis as a small macular hyperpigmentation on the face, especially the malar areas and the both sides of the forehead. The color of lesion is mostly blotchy gray to blue. Treatment is not necessary for Hori's nevus except cosmetic concerns. However treating the Hori's nevus without side effects such as purpura, crust, postinflammatory hyperpigmentation and scarring is extremely difficult. Therefore, the authors introduce a new combination treatment using Dr. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We believe that the combination therapy of Dr. Hoon Hur's GPT and Dr. Hoon Hur's OMS-1 PT using a high fluence 1064 nm QSNL is safer and more effective for the Becker's nevus treatment compared to traditional laser therapies. Authors from previous research papers claimed that treatment using Dr. Hoon Hur's GPT with a high 1064 nm QSNL was extremely effective and did not cause any harmful side effects such as scarring, PIH, or mottled hypopigmentation in other various pigmentary skin diseases including café au lait spots [12][13][14][15][16], Becker's nevus [13], partial unilateral lentiginosis [13,17], Ota's nevus [18], Hori's nevus [19], congenital melanocytic nevus [20], Riehl's melanosis [21], erythema ab igne [22], and pruigo pigmentosa [23]. We surmise a fusion of Dr. Hoon Hur's GPT and Dr. Hoon Hur's OMS-1 PT, being performed routinely without damage to the epidermis on a weekly basis, leads to gradual destruction of epidermal melanocytes and dermal smooth muscles, therefore causing apoptotic melanocytic cell death program and apoptotic smooth muscle cell death program.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the combination therapy of Dr. Hoon Hur's GPT and Dr. Hoon Hur's OMS-1 PT using a high fluence 1064 nm QSNL is safer and more effective for the Becker's nevus treatment compared to traditional laser therapies. Authors from previous research papers claimed that treatment using Dr. Hoon Hur's GPT with a high 1064 nm QSNL was extremely effective and did not cause any harmful side effects such as scarring, PIH, or mottled hypopigmentation in other various pigmentary skin diseases including café au lait spots [12][13][14][15][16], Becker's nevus [13], partial unilateral lentiginosis [13,17], Ota's nevus [18], Hori's nevus [19], congenital melanocytic nevus [20], Riehl's melanosis [21], erythema ab igne [22], and pruigo pigmentosa [23]. We surmise a fusion of Dr. Hoon Hur's GPT and Dr. Hoon Hur's OMS-1 PT, being performed routinely without damage to the epidermis on a weekly basis, leads to gradual destruction of epidermal melanocytes and dermal smooth muscles, therefore causing apoptotic melanocytic cell death program and apoptotic smooth muscle cell death program.…”
Section: Discussionmentioning
confidence: 99%
“…The authors devised a new treatment using a Dr.Hoon Hur's GPT with a high fluence1064nm QSNL (StarWalkerLaser, Fotona, Slovenia).The parameters were a spot size of 7 mm, a fluence of 2.2 J/cm 2 and a pulse rate of 10Hz with one pass by a sliding-stacking technique over the infantile CALS at intervals of one week.We believe that Dr. Hoon Hur's GPT using a high fluence 1064 nm QSNL is safer and more effective than the traditional CALS treatments [12][13][14][15]. In previous papers, the authors also reported that Dr. Hoon Hur's GPT using a high 1064 nm QSNL is a very effective therapy without harmful side effects such as PIH, mottled hypopigmentation or scarring in various pigmentary skin diseases such as café au lait spot [12][13][14][15], partial unilateral lentiginosis [13,16], Becker's nevus [13], Ota's nevus [17], Hori's nevus [18], congenital melanocytic nevus [19], Riehl's melanosis [20], erythema ab igne [21] and prurigo pigmentosa [22]. We think that Dr. Hoon Hur's GPT, which is performed regularly on a weekly basis with minimal damage to the epidermis, promotes gradual destruction of melanocytes in the epidermis or dermis, leading to apoptotic melanocytic cell death program [12][13][14][15].Due to the poor absorption by epidermal melanin, Dr. Hoon Hur's GPT with the adoption of high fluence 1064-nm QSNL is able to destroy the melanosomes in the epidermal melanocytes with minimal epidermal damage, finally causing epidermal melanocytes to lose functions and turn into ghost cells [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%